2016
DOI: 10.1161/circresaha.116.308964
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoded Biosensors Reveal PKA Hyperphosphorylation on the Myofilaments in Rabbit Heart Failure

Abstract: Rationale In heart failure, myofilament proteins display abnormal phosphorylation, which contributes to contractile dysfunction. The mechanisms underlying the dysregulation of protein phosphorylation on myofilaments is not clear. Objective This study aims to understand the mechanisms underlying altered phosphorylation of myofilament proteins in heart failure. Methods and Results We generate a novel genetically encoded protein kinase A (PKA) biosensor anchored onto the myofilaments in rabbit cardiac myocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 42 publications
2
58
2
Order By: Relevance
“…Hence, we assume Cav-3 dissociation to be partially responsible for the reorientation of T-tubules into the longitudinal direction. A recent publication studied HF in rabbit after ∼7.1 months of aortic insufficiency and constriction 38 . In this rabbit model a Cav-3 protein reduction was shown together with an increased β 2 AR signal in the myofilament compartment of cardiomyocytes and unaltered signalling levels at the sarcoplasmic reticulum (SR) and plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we assume Cav-3 dissociation to be partially responsible for the reorientation of T-tubules into the longitudinal direction. A recent publication studied HF in rabbit after ∼7.1 months of aortic insufficiency and constriction 38 . In this rabbit model a Cav-3 protein reduction was shown together with an increased β 2 AR signal in the myofilament compartment of cardiomyocytes and unaltered signalling levels at the sarcoplasmic reticulum (SR) and plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an additional study utilizing a rabbit model, also showed that reintroduction of caveolin-3 was able to normalizes β-adrenergic-induced contractile responses in HF myocytes, while also showing that in HF β2-induced signaling gains access to myofilament which may contribute to abnormal PKA phosphorylation of troponin I and contractile dysfunction ( Barbagallo et al, 2016 ). In addition, work from the Sacconi group has shown that while cells from HF myocytes respond to β-adrenergic stimulation, this is not the case at the T-tubules that do not conduct APs, where the alterations seen in response may be caused by a lack of electrical activity.…”
Section: Heart Failure and Afterdepolarizationsmentioning
confidence: 99%
“…Genetically encoded cAMP and PKA-activity sensors can be engineered to localise at defined cellular sites by introducing a unique targeting sequence (DiPilato et al, 2004;Di Benedetto et al, 2008;Herget et al, 2008;Di Benedetto et al, 2013;Sprenger et al, 2015;Barbagallo et al, 2016;Surdo et al, 2017). Targeting the same cAMP FRET reporter to the plasma membrane and the mitochondria revealed differential dynamics of cAMP signalling in these two compartments.…”
Section: Defining Camp Nanodomains Using Real-time Imagingmentioning
confidence: 99%
“…We are only beginning to understand the components of signalosomes in different cell types and cellular compartments (Maurice et al, 2014). We predict that combining advanced imaging methods, such as live cell fluorescence microscopy using targeted reporters (Barbagallo et al, 2016;Surdo et al, 2017) and super-resolution imaging (Ni et al, 2018), with proteomics approaches will be instrumental in identifying additional signalling components and novel signalosomes.…”
Section: Introductionmentioning
confidence: 99%